Contributo ao estudo da formação e intervenção profissional em Educação Física: categorias exploração e formação humana em evidência - Maia, Júlio César Apolinário (Revista Cocar, 2020)
Study contribution to formation and professional intervention in Physical Education: exploration and human formation categories in evidence Resumo O presente estudo investiga o movimento de retrocesso enfrentado por uma Instituição de Ensino Superior (IES) pública do Estado de Goiás a partir de um processo de revisão curricular. Ampara-se, metodologicamente, no Materialismo Histórico Dialético e adota a Análise de Conteúdo para análise de dados. Constata, por meio da resposta dos docentes/egressos entrevistados, o enaltecimento da categoria exploração e a perca do sentido dado à categoria formação humana no âmbito da formação e intervenção profissional em Educação Física. Palavras-chave: Diretrizes Curriculares Nacionais. Educação Física. Formação humana. Abstract The present study investigates the setback movement faced by a public Higher Education Institution in the Goiás State based on a curriculum review process. Methodologically, it relates to Dialectical Historical Materialism and Content Analysis for data analysis. It apprehends, through the teachers/graduates interviewed response, the diffusion of exploration category and the loss of meaning given to the human formation category in the context of formation and professional intervention in Physical Education. Keywords: National Curriculum Guidelines. Physical Education. Human formation.